Adoption of Marketing Technology and Its Influence on the Profits of MSMEs in Kauman Batik Village - Dwijayanto, Danang Hilman; Sutianingsih, Sutianingsih (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of technology can support business advancement. Adopting marketing technology makes business production more efficient, so profits are optimal. This study aims to examine the implementation of marketing technology and its impact on the profits of batik MSMEs in Kauman Batik Village. Given that the COVID-19 pandemic crisis is over, the impact on MSMEs has not fully recovered. The analysis uses linear regression with cross-sectional data and accidental sampling techniques. The results show that the adoption of marketing technology, business capital, length of business, number of workers, and business location have a significant positive effect on batik profits. Therefore, it is recommended that business actors can improve the quality of human resources (HR) as workers in implementing marketing technology.